Changing patterns in hotel room demand – case study of the Aquaticum Debrecen Thermal and Wellness Hotel - Hevessy, Gábor (Applied Studies in Agribusiness and Commerce, 2011)
Aquaticum Debrecen Thermal and Wellness Hotel is a very successful lodging property not only in Debrecen but also in the Northern Great Plain Region and in the Eastern part of Hungary and in point of fact in Hungary. In the past years Aquaticum Thermal and Wellness Hotel has been the leader in the region by revenue per available rooms (RevPAR). RevPAR indicates the overall performance of properties, accordingly it is the most commonly used statistical indicator in comparison to competitors in Hotel industry. In the past years, demand for Hotel rooms has changed. This changing has several signs. For instance the occupancy rate, the rate of domestic and foreign guests, the nationality of foreign guests, the time between booking and travelling, and many other demand patterns have changed. During the last year, the changing has been accelerated by the global economic crisis. Guests are waiting with their bookings hoping for better rates and last minute offers. The forecast of demand became much harder than ever before. These forecasts are basic ingredients of the revenue management systems, which systems are in use or will be in use by Hungarian Hotels. These systems are necessary to keep RevPAR at a higher level and to help Hotels to achieve better performance.